2018
DOI: 10.1021/acsami.8b15545
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Composite Networks with Ultrathin Skin Layers of Graphene Film for Exceptional Electromagnetic Interference Shielding

Abstract: Natural cotton was selected as a cheap and renewable carbon source to fabricate novel carbon networks with porous three-dimensional conductive frameworks composed of numerous unique hollow carbon fibers by pyrolysis, and outstanding electromagnetic interference (EMI) shielding effectiveness (SE) of ∼26.9–46.9 dB was observed for the samples (∼0.3 mm in thickness) with density of ∼0.14–0.06 g/cm3. Moreover, the combination of cotton-derived carbon networks with graphene through the construction of a sandwich co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…36,37,45,46 Moreover, the effect of different CCB type on ultimate shielding performance was also investigated (Figure 3B), and interestingly, the SE total decreased from ∼82.0 dB for 1500-A to ∼65.3 and ∼55.3 dB for 1500-B and 1500-E composites owing to the slight weakening of EM-reflection and strengthening of EM-absorption (R↓ and A↑, Figure 3C). It may be because that, though the first microwave-reflection at the input interface is similar on account of their similar electrical properties, the microwave penetrating the inner sawtooth with longer side (A > B > E-type) can be dissipated more effectively based on our previous study, 36 which may lead to less microwave to interact with the first-reflected microwaves by constructive interference between two parallel surfaces, 37,38,45 and thus, stronger total EM-reflection could be detected for the A-type CCB sample. The weaker EMabsorption can also be observed if the energy-dissipation caused by the inner sawtooth structure is weaker than that induced by constructive interference.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…36,37,45,46 Moreover, the effect of different CCB type on ultimate shielding performance was also investigated (Figure 3B), and interestingly, the SE total decreased from ∼82.0 dB for 1500-A to ∼65.3 and ∼55.3 dB for 1500-B and 1500-E composites owing to the slight weakening of EM-reflection and strengthening of EM-absorption (R↓ and A↑, Figure 3C). It may be because that, though the first microwave-reflection at the input interface is similar on account of their similar electrical properties, the microwave penetrating the inner sawtooth with longer side (A > B > E-type) can be dissipated more effectively based on our previous study, 36 which may lead to less microwave to interact with the first-reflected microwaves by constructive interference between two parallel surfaces, 37,38,45 and thus, stronger total EM-reflection could be detected for the A-type CCB sample. The weaker EMabsorption can also be observed if the energy-dissipation caused by the inner sawtooth structure is weaker than that induced by constructive interference.…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…The 800-A composite had a SE total of ∼46.0 dB, and this value is improved to ∼60.7 dB for 1000-A composite and further to ∼82.0 dB for 1500-A composite, which is in accordance with the reported results of biomass-derived MCAs presenting a continuous increment with the elevated carbonization temperature by reason for the enhancement of electrical properties (the very similar results could be obtained for XXX-B and XXX-E composites in Figure S4 as well). 14,38 To the best knowledge, the EMI SE of ∼46.0−82.0 dB signified the effective attenuation of ∼99.997−99.9999993% incident microwaves, far surpassing the SE requirements for civilian applications and close to military standards. Their R-A coefficients of ∼0.701− 0.904 and ∼0.298−0.095 (Figure 3C) suggested that such prominent EMI-shielding capability should ascribe to the strong microwave-reflection originating from the large impedance mismatch at the interface, 23,44 as well as the weak microwave-absorption relating to the conduction loss together with the special construction capable of internal multiple reflections (scattering) and constructive interference (the constructive interference would happen when multiple reflections are aligned between two parallel carbon sheets in the CCB samples).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the fact that 3DIGC-750 presents the highest electrical conductivity (the average value is as high as ≈1265.8 S m −1 ) among 3DIGCs has been demonstrated by the experimental measurement, as shown in Figure 5c. This impressive conductivity is even much higher than those of most graphene electromagnetic shielding materials and graphene electrode materials, [56,57] which can undoubtably be ascribed to the elaborate interconnected scaffold of samples. An interesting phenomenon noticed is that 3DIGC-800 shows a relatively moderate electrical conductivity (average ≈833.3 S m −1 ), despite having the highest graphitization degree.…”
Section: Resultsmentioning
confidence: 94%
“…For ceramic‐based heat dissipation materials, the complex processing technology and high processing temperature lead to their high cost. For metal‐based heat dissipation materials, they generally show poor chemical resistance 4,5 . Meanwhile, metal‐based components possess high electrical conductivity, which significantly attenuate electromagnetic waves and interfere with signals during the use of electronic equipment.…”
Section: Introductionmentioning
confidence: 99%